A genetic risk score is significantly associated with statin therapy response in the elderly population. Issue 3 (12th December 2016) - Ciuculete, D.M.; Bandstein, M.; Benedict, C.; Waeber, G.; Vollenweider, P.; Lind, L.; Schiöth, H.B.; Mwinyi, J.
Abstract : The ability of statins to strongly reduce low‐density lipoprotein cholesterol (LDL‐C) varies interindividually and is partially influenced by genetic variants. Based on a comprehensive analysis of 23 single nucleotide polymorphisms (SNPs) known to be associated with pharmacokinetics and dynamics of statins, we developed a genetic risk score to study its impact on the therapy outcome in elderly individuals under at least 5 years statin therapy. The study was performed in a population‐based cohort of 1016 elderly individuals, which comprised 168 statin users investigated at age 75 and 80. Using random forest models, the major variants influencing LDL‐C levels were summarized in a weighted GRS (wGRS). The wGRS was tested with lipid and glucose outcomes and validated in an independent population‐based cohort including 221 statin users. Four SNPs within the APOE cluster (rs7412, rs4420638), ABCC2 (rs2002042) and CELSR/SORT1/PSRC1 (rs646776), displayed a major impact on statin efficacy. The wGRS was significantly associated with lower LDL‐C at age 75 and 80. This association was replicated displaying similar results. GRS analysis is a powerful tool to evaluate the additive effects of genetic variants on statin response and to estimate the magnitude of LDL‐C reduction to a considerable extent in the older population. Abstract :